Assessment of the percutaneous endoscopic gastrostomy feeding tube as part of an integrated approach to enteral feeding. Issue 5 (May 1992) - Wicks, C; Gimson, A; Vlavianos, P; Lombard, M; Panos, M; Macmathuna, P; Tudor, M; Andrews, K; Westaby, D
Abstract : The insertion of percutaneous endoscopic gastrostomy has been well documented. The possible benefits for patient nutrition and nursing practice have, however, not been assessed. We report a study of enteral feeding by percutaneous endoscopic gastrostomy in 30 patients, the majority with a persistent vegetative state. All patients had previously been fed through a nasogastric tube using manual administration and a dietitian assessed protein calorie intake. Based upon body mass index (weight/height2), midarm circumference and triceps skinfold thickness, 20 (67%) were malnourished, with 10 patients having a body mass index less than 17 (severe malnutrition); attributed to high rates of both tube displacement and feed regurgitation. Patients were observed over six to 12 months after percutaneous endoscopic gastrostomy insertion combined with overnight continuous pump feeding. All patients attained a body mass index greater than 17, and 17 (56%) of the total number achieved the normal range with no change in protein-calorie intake (pre: 2110 kcal, post: 1880 kcal). Complications of percutaneous endoscopic gastrostomy in the study group included peritonitis (one), tube site infection (two) and displacement (two); all without serious sequelae. As part of an integrated approach percutaneous endoscopic gastrostomy proved a safe and efficient method of enteral feeding and justifies wider consideration in the United Kingdom.